Salidas pedagógicas para descubrir el medio natural y cultural en niños de 5 a 6 años de la escuela de educación básica 18 de noviembre de la ciudad de Loja del año lectivo 2018-2019. - Montalvan Yaguana, Erika Johanna (2020)
The research called: PEDAGOGICAL OUTPUTS TO DISCOVER THE NATURAL AND CULTURAL ENVIRONMENT IN CHILDREN FROM 5 TO 6 YEARS OF THE BASIC EDUCATION SCHOOL NOVEMBER 18 OF THE CITY OF LOJA OF THE LECTIVE YEAR 2018-2019, where the general objective was to determine how the outputs Pedagogics allow discovering the natural and cultural environment in children from 5 to 6 years old; The following methods were used: the scientific, the experimental, inductive and deductive; Among the techniques and instruments were present: the survey aimed at the 6 first-year teachers, a rating scale that was applied to 22 first-year students of basic education, which allowed diagnosing the problem, identifying that: 27% of the children were at the beginning of acquiring knowledge about living beings, professions, properties of matter, traditions and customs, the senses; 36% in the acquisition process and 36% in the acquired one; After applying the alternative proposal “With my hands and my feet, I know everything my environment is”, significant changes were reflected in which 20% of those surveyed rose to the acquired level and 80% acquired knowledge in discovering the natural and cultural environment. It is concluded that pedagogical outputs as a methodology based on learning experiences favor the development of knowledge of the natural, cultural and social environment.